Online dictionary learning for car recognition using sparse coding and LARS - Ilias Kamal; Khalid Housni; Youssef Hadi (IAES International Journal of Artificial Intelligence (IJ-AI), 2020)
The bag of feature method coupled with online dictionary learning is the basis of our car make and model recognition algorithm. By using a sparse coding computing technique named LARS (Least Angle Regression) we learn a dictionary of codewords over a dataset of Square Mapped Gradient feature vectors obtained from a densely sampled narrow patch of the front part of vehicles. We then apply SVMs (Support Vector Machines) and KMeans supervised classification to obtain some promising results.